Towards Achieving Zero Hunger Among UUM Community via Smart Food Bank Application - Earn, Tan Jia; ChePa, Noraziah (Multidisciplinary Applied Research and Innovation, 2023)
The Student's Food Bank at Universiti Utara Malaysia has been launched in September 2019. It is officiated by His Majesty the Sultan of Kedah. It is operated manually. Due to the large number of donations received, it is difficult to run the food bank effectively, especially when it comes to helping students who are truly in need. A smart food bank application is created and developed in a mobile environment and operates on the Android platform with the goal of having an effective management of the food bank in order to achieve zero hunger in the UUM community. A smart food bank application is created and developed in a mobile environment and operates on the Android platform with the goal of having an effective management of the food bank in order to achieve zero hunger in the UUM community. The management of food stock, food allocation, food application, food contributions, as well as the management of registered users, are the primary functions included in the application. Users of the application can check the status of their applications and request food by sharing their location on the UUM map. By indicating their preferred place for the administrator to pick them up, potential donors can provide their donation. All tasks are created to make it easier for these three key partners to administer the UUM food bank better. The project supports the Sustainable Development Goals' (SDG) second and third objectives, which are respectively to end hunger and promote health and well-being. It can act as a platform for giving the UUM community healthy meals so that the desired SDG targets can be met. This innovative food bank application is believed to be able to help organize a proper food distribution programme for the UUM community's less fortunate members, which could eventually improve the students' quality of life. The smart food bank application can be extended to additional food bank facilities or comparable organisations providing the same services in order to achieve zero hunger in a larger context due to its good findings, feedback, and impacts.